A Review of Consumer Adoption of Rooftop Solar PV in India and Effective Frameworks - Satapathy, Amitabh; Jain, Arvind Kumar; Barthwal, Sunil (Indian Journal of Marketing, 2019)
It is always intriguing to know how and why individuals adopt innovations. This paper found out the variables that lead to adoption of rooftop solar PV and proposed a model that could explain the factors behind adoption of rooftop solar PV in India. The framework is very unique in nature as no such model is available exclusively for rooftop solar PV adoption and no research is available to find out the factors that lead to its adoption. Just like Rogers’s theory of adoption, this paper also found out five key factors for adoption of rooftop solar PV systems. It identified all possible variables from an exhaustive literature review and then grouped them into five key factors that adopters considered for adoption of rooftop solar PV systems. Using the proposed model, it would be possible to identify the reasons for the poor adoption of rooftop solar PV in India so far and a possible roadmap to meet India’s ambitious target of 40 GW rooftop solar PV adoption by the year 2022. The paper also explained the current energy scenario of the country and also the status of rooftop solar PV with respect to leading countries using descriptive statistics. The paper offered future research opportunities and spelled out the limitations as well. The research was carried out in May and June 2018.